More Than Marketing: The Role of Emotional Intelligence in Social Media for Medical Tourism - Yawei Wang (Visions in Leisure and Business)
The medical tourism experience is increasingly shaped not just by clinical quality and cost, but also by how patients emotionally connect with their providers. The journey begins long before they ever step foot in a medical facility, which is often far from home. Social media serves as a powerful interface for prospective patients to evaluate care, communicate needs, and gain reassurance. This manuscript proposes a conceptual framework that integrates Goleman’s Emotional Intelligence (EI) model with the Uses and Gratifications Theory (UGT) to explain how medical tourism providers create value through emotionally intelligent online communication. Based on qualitative analysis of user-generated content and provider responses across multiple platforms, the framework identifies key emotional touchpoints in the medical tourism journey. It clarifies how EI-driven interactions influence trust, satisfaction, and behavioral intentions.